Antimony pollution threatens soils and riverine habitats across China: An analysis of antimony concentrations, changes, and risks - Liu, Lianhua (2023)
The adverse effects of antimony (Sb) pollution on ecosystems and human health caused by its use, enrichment, and bioaccumulation have become global environmental problems, particularly in China. Based on a scientometric analysis of the research topics and evolution of Sb pollution, 210 peer-reviewed articles across 264 locations in China were selected to analyze Sb concentrations, changes, and risks in different environments (i.e., soil, sediment, and water). Substantially elevated concentrations were reported in the chosen environments throughout the studied literature, with approximately 36.6%, 41.3% and 20.8% of the soil, water and sediment sampling sites, respectively, exceeding the national and international guidelines. Although Sb concentrations were stable in water and sediment, those in soil slightly increased slightly over the past two decades. The majority of studies and the highest Sb concentrations were typically concentrated in Hunan, Guangxi, and Guizhou, where most Sb deposits and intensive mining and smelting activities are concentrated. A temporal analysis over three crucial periods of the Sb industry further indicated that Sb concentrations and pollution had increased in several provinces in recent years. The estimated risk quotient, using Monte Carlo simulations, indicated that species were markedly affected by Sb contamination, with 21.6% of events occurring in the high-risk category. The ingestion of contaminated soils posed the highest potential health risk to the population, with 47.9% of the events indicated to represent at least a low risk. Risks of water ingestion were estimated to exist in 4.9% of the simulated exposure events. More environmental campaigns for Sb pollution control are urgently needed, especially in Sb hotspots, to reduce environmental pressure and avoid direct and indirect hazards to organisms and populations.